2017
DOI: 10.3390/molecules22020311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anti-Inflammatory Activities of Supercritical Carbon Dioxide versus Ethanol Extracts from Leaves of Perilla frutescens Britt. Radiation Mutant

Abstract: In this study, we aimed to compare supercritical carbon dioxide extraction and ethanol extraction for isoegomaketone (IK) content in perilla leaf extracts and to identify the optimal method. We measured the IK concentration using HPLC and inflammatory mediators in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells from the extracts. The IK concentration was 10-fold higher in perilla leaf extracts by supercritical carbon dioxide extraction (SFE) compared with that in perilla leaf extracts by ethanol extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…IK was isolated from the supercritical carbon dioxide (SC-CO 2 ) extract, a radiation-induced mutant cultivar of Perilla frutescens var. crispa [ 23 ]. Specific antibodies for p44/42 MAPK (ERK1/2), phospho (p)-p44/p42 MAPK (ERK1/2) (Thr202/Tyr204), SPK/JNK, p-JNK (Thr183/Tyr185), p38 MAPK, and p-p38 MAPK (Thr180/Tyr182) were purchased from Cell Signaling Technology (Cell Signaling Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…IK was isolated from the supercritical carbon dioxide (SC-CO 2 ) extract, a radiation-induced mutant cultivar of Perilla frutescens var. crispa [ 23 ]. Specific antibodies for p44/42 MAPK (ERK1/2), phospho (p)-p44/p42 MAPK (ERK1/2) (Thr202/Tyr204), SPK/JNK, p-JNK (Thr183/Tyr185), p38 MAPK, and p-p38 MAPK (Thr180/Tyr182) were purchased from Cell Signaling Technology (Cell Signaling Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, methods based on reversed-phase LC with C8 and C18 columns have been reported for polar terpene derivatives (caryophyllene oxide, γ-oryzanol, tocotrienol and tocopherol, senkyunolide, isoegomaketone-IK), phenolic compounds (quercetin, kaempferol and resveratrol, myricetin, isorhamnetin) and alkaloids (piperine). In this HPLC-based methods, UV detection is the most popular choice [32,34,[60][61][62][63][64]. However, the need of standards is here mandatory for an adequate identification of compounds by HPLC-UV.…”
Section: Phytochemical Profiling Of Natural Antiviral and Anti-inflammatory Compoundsmentioning
confidence: 99%
“…In the comparison studies of LPS-induced anti-inflammatory activities and chemical profiles of the SC-CO 2 extract of PFCA versus PFC [ 19 ] and the SC-CO 2 versus the ethanol extracts of PFCA [ 20 ], the SC-CO 2 extract of PFCA showed greater potency and higher content of 2 and 3 than the SC-CO 2 extract of PFC and the ethanol extract of PFCA. The HPLC chromatogram of these three extracts showed an unknown peak besides the two main peaks for 2 and 3 , and thus it was identified as compound 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous biological evaluations on 2 , this compound was found to have anticancer [ 7 ], anti-inflammatory [ 9 ], and antioxidant activities [ 10 ]. Recently, we reported that the PFCA extract by supercritical carbon dioxide (SC-CO 2 ) extraction method contained the increased content of monoterpenes and enhanced anti-inflammatory effect, compared to those of the SC-CO 2 extract of the original cultivar (PFC) [ 19 ] as well as the ethanol extract of PFCA [ 20 ]. SC-CO 2 extraction technology has been recognized as a powerful technique for essential oils from oil bearing plant sources [ 21 ], with advantages of being non-toxic, non-flammable, time and cost-effective, and more environmentally friendly [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation